1968
DOI: 10.1111/j.1432-1033.1968.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of C19‐Steroids in Rat Liver

Abstract: The formation of androstanetriols after incubation of testosterone with 105,000 x g microsomes of adult male rat liver was investigated. The steroids were isolated by thin-layer chromatography and were identified by gas chromatography-mass spectrometry as 5 a-androstane2p,3a,l7p-triol, 5u-androstane-3a,7a,l7,!?-triol and 5a-androstane-3a(and 3/?),16~,17p-triol. Incubation of 2p-and 7a-hydroxytestosterone only gave androstanetriols with a 3a-configuration while incubation with 6,9-and 16a-hydroxytestosterone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…When an additional TMSO group is present at the 3‐position ( 132 ), the situation changes and a group of three ions ( m/z 129, 142 and 143) appear (Fig. b, a contribution to m/z 129 ( n ) is from the D‐ring), said to be typical of steroids with 2‐TMSO groups (Eriksson & Gustafsson, ; Gustafsson et al, ). These ions are also prominent in the spectra from 2α,3α‐dihydroxy‐pregnan‐20‐one (Eriksson et al, ) and 2β,3β,17β‐trihydroxy‐5α‐androstane TMS ether.…”
Section: Trimethylsilyl Derivativesmentioning
confidence: 99%
See 3 more Smart Citations
“…When an additional TMSO group is present at the 3‐position ( 132 ), the situation changes and a group of three ions ( m/z 129, 142 and 143) appear (Fig. b, a contribution to m/z 129 ( n ) is from the D‐ring), said to be typical of steroids with 2‐TMSO groups (Eriksson & Gustafsson, ; Gustafsson et al, ). These ions are also prominent in the spectra from 2α,3α‐dihydroxy‐pregnan‐20‐one (Eriksson et al, ) and 2β,3β,17β‐trihydroxy‐5α‐androstane TMS ether.…”
Section: Trimethylsilyl Derivativesmentioning
confidence: 99%
“…Proposed mechanisms for their formation, consistent with labeling data, are shown in Schemes and respectively. However, the ions do not appear in the spectra of some more highly‐substituted steroids such as those containing 17‐TMSO and 17 C═O groups (Gustafsson & Lisboa, , , , ; Gustafsson et al, ).…”
Section: Trimethylsilyl Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…In an early study by Wostmann et al (17), it was shown that GF rats on a restricted diet had a serum testosterone level that was 2.5 times higher than in Conv rats. It is well established that the presence of intestinal microbial ora gives rise to metabolites of testosterone, which are not found in GF counterparts (25). Whether these metabolites exert altered androgenic stimuli other than testosterone itself has not been satisfactorily investigated.…”
Section: Microbial Statusmentioning
confidence: 99%